Replication of short selling In Islamic finance - Hasan, Aznan; Khan, Sarfaraj (IIUM Press, 2015)
This paper discusses short-selling and its implication in Islamic capital markets as this has always been a subject of debate. The practice of short-selling in capital markets is considered a tool for providing liquidity and better price discovery to the traders. The use of short-selling in Islamic capital markets is objectionable. The factors that make short-selling non-Shari’ah compliant are: (I) speculation that mostly verges on gambling, (ii) interest, and (iii) its contraven maslahah (public interest), that is, it may result in market manipulation and could potentially wreak havoc on the market. Therefore, the main objective of this paper is to review the structure of short-selling from the Shari’ah perspective. There are mainly six Shari’ah contracts discussed in this paper that can conveniently be used for structuring Shari’ah compliant short-selling. These Shari’ah contracts are: urbun, wa’ad, wakalah, mudharabah, bai’ salam and musharakah.